The voice recognition system as a way of accessing the computer for people with physical standards as usual. - Alcantud F; Dolz I; Gaya C; Martín M (Technology & Disability, 2006)
This article introduces the results of an evaluation of a voice recognition system used as a tool for computer access in dictation activities. The software was applied to three groups: motor-disabled people suffering severe speech disorders; motor-disabled people without speech difficulties and a third, control group of non-disabled people. We found evidence that the tool results are acceptable, as task performance improves as both the subject and the system receive training. The system showed similar performance for the three groups. It also had an intrinsic rehabilitating value for those with speech disorders, as the system's feedback forced them to improve their pronunciation.